2022
DOI: 10.24200/sci.2022.56935.4998
|View full text |Cite
|
Sign up to set email alerts
|

Road Map to BIM Use for Infrastructure Domains: Identifying and Contextualizing Variables of Infrastructure Projects

Abstract: Nowadays, construction activities and projects are becoming much more challenging to manage.Being involve with different stakeholders is a difficult task and information and communication technology (ICT) has been addressed as a solution. On the other hand, Building Information Modeling (BIM) has already taken first steps towards this big revolution and gained a place in the sector. By inspiration from modality of BIM, there can be an adoption to other sub-branch of construction industry such as infrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The current trend in this field is the development and standardisation of BIM for infrastructure, primarily driven by specialists in architecture and civil engineering who have recognized the benefits of using these tools in managing building projects. Consequently, numerous government transport bodies are now crafting roadmaps for the implementation of infrastructure BIM (Ghasemzadeh et al, 2022;Borrmann et al, 2021). However, this BIM-centric approach proves sufficient for managing buildings but falls short when it comes to linear infrastructures (Garramone et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current trend in this field is the development and standardisation of BIM for infrastructure, primarily driven by specialists in architecture and civil engineering who have recognized the benefits of using these tools in managing building projects. Consequently, numerous government transport bodies are now crafting roadmaps for the implementation of infrastructure BIM (Ghasemzadeh et al, 2022;Borrmann et al, 2021). However, this BIM-centric approach proves sufficient for managing buildings but falls short when it comes to linear infrastructures (Garramone et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many countries in Europe and North America have also developed road maps to outline the digitalisation of transport structures (Borrmann et al, 2021). While the deployment of BIM for infrastructure is useful for managing structures such as buildings, its deployment for transport infrastructure remains complex due to several barriers (Ghasemzadeh et al, 2022). However, Garramone et al (2020) demonstrated that the integration of GIS and BIM could benefit the management of infrastructure such as roads.…”
Section: Introductionmentioning
confidence: 99%